Peningkatan Aktivitas dan Hasil Belajar IPA Melalui Pembelajaran Daring dengan Media Audio Visual - Dian Okta Wulandari; Tri Ariani; Elya Rosalina (SPEJ (Science and Physic Education Journal), 2021)
Abstract: The purpose of this study was to increase student activity and learning outcomes using audio-visual media in fourth-grade students of SD Negeri 15 Lubuklinggau. This research method is classroom action research. This study's data collection techniques used tests, checklist (Ö) observation sheets, and documentation. Classroom action research is a cycle whose activities consist of 4 stages, 1) planning, 2) implementing actions, 3) implementing observations, 4) data reflection. The subjects of class IV SD Negeri 15 Lubuklinggau totaled 23 students consisting of 14 boys and nine girls. Based on the results of data analysis, it is known that the use of audio-visual media in online learning can increase the activity and learning outcomes of fourth-grade students. In the pre-action, students' completeness was 26.08%, with an average value of 65.43. Students' completeness increased to 52.17% in the first cycle, with an average value in the first cycle of 69.34. In the second cycle, students' mastery increased with a percentage value of 91.30% with an average value of 75.65. Thus the classical mastery value of students has reached learning mastery of 75%. Student learning activities also increased with an average percentage in the first cycle of 63.69% and 70.34% in the second cycle. In conclusion, audio-visual media can increase student activity in class IV SD Negeri 15 Lubuklinggau, with the average score of student learning activities increasing from the process I to cycle II. Keywords: Learning Outcomes and Activities, Audio-Visual Media, Improvement